Awareness, attitude, participation and use of technology in birth preparedness and complication readiness among husbands of women availing obstetric care at a rural maternity hospital in South Karnataka - Kalliath, Jacob Davies; Johnson, Avita R.; Pinto, Priya; James, Nidhi; Sebastian, Victoria (International Journal Of Community Medicine And Public Health, 2019)
Background: Birth preparedness and complication readiness (BPCR) is an evidence-based strategy to reduce maternal mortality. Husbands have an important role to play in birth preparedness. There is paucity of data regarding husband’s participation and the use of technology in BPCR. The objective is to assess awareness, attitudes and the use of mass media and technology in BPCR among husbands of women availing obstetric care at a rural maternity hospital. Methods: A cross-sectional study was conducted in a rural maternity hospital in Ramanagara district, Karnataka. Husbands of women of more than 28 weeks of gestation, or postnatal mothers up to 6 weeks after delivery were included in the study. Results: Of the 133 participants, only 37.6% of the husbands had adequate awareness of BPCR, 62.4% had adequate participation in BPCR. Husbands’ participation was highest in saving money for delivery (75.9%), and lowest for arranging a blood donor (27.8%). Commonest source of information regarding BPCR was mobile phone (30.8%). Husbands awareness of BPCR was associate with reading MCP card OR=5.36 (2.47-11.63), seeing BPCR- related posters in hospital OR=6.59 (1.32-33.13) and using mobile phone for accessing BPCR-related information OR=2.28 (1.07-4.85). Husbands participation in BPCR was associated with awareness of BPCR OR=3.72 (1.65-8.41) and accompanying wife for antenatal visits OR=2.84 (2.25-3.59). Only one third of husbands felt it necessary to accompany their wife for antenatal visits or delivery. Conclusions: The MCP card and mobile phone technology may be further tapped to improve husband’s awareness and participation in BPCR, besides encouraging men to accompany their wife for antenatal visits.